Revalution and Reconstruction of the Maritime Historiography in Southeast Asia Archipelago - Ismail Ali; MOSLI TARSAT; Douglas Nyeging Taong (International Journal of Business and Social Science Research, 2024)
Seas and oceans are equally realms with their advantages in bridging nations, inculcating a sense of unity, mutual understanding, and cooperation as well as in generating wealth. They are considered priceless treasures, which can neither be exchanged nor modified. At the same time, seas and oceans are also capable of changing their function as theaters of conflict and routes towards colonization/imperialism that has ultimately led to the demise of various ancient kingdoms. In the historiography of the Southeast Asia Archipelago, the relationship between men known as seafarers and seas like the South China Sea, Sulu Sea, Celebes Sea, Flores Sea, Jawa Sea, Banda Sea, and others, all of which are within the confines of the Indian and Pacific oceans, is indisputable. It is not far-fetched to suggest that the change and development in present-day Southeast Asia, from traditional kingdoms to modern nation-states are intimately rooted in and shaped by the contributions of our seafaring ancestors. History demonstrates how they risked as well as sacrificed their lives crossing treacherous waters and encountering stormy weathers just to ensure their legacy and continuity of the future generations of seafarers, and turning this region into an epicentre that was second to none in the world of civilizations. Yet, their thousands of years of contributions and sacrifices appear trivial and pale into insignificance like” shipwrecks laying at the bottom of the sea in their forgotten watery graves”. This article aims to discuss the diversity of terminology and fields in maritime historiography; the glory of the maritime kingdoms in the Southeast Asia Archipelago as leading powers, emporiums, and empires; and to reevaluate and reconstruct the facts of maritime history in the Southeast Asia Archipelago.